Impact of Integrated Herbicide Hand Weeding Practices and Nitrogen Rates Enhance Weed Control and Seed Yield of Sesame (Sesamum indicum L.) under Semi Arid, Loamy Sandy Soils - , Pinki Dadarwal; , G.L. Yadav (Archives of Current Research International, 2025)
A field experiment was conducted on loamy‑sandy soil during the kharif season. The factorial RBD trial comprised seven weed‑management treatments: weedy check; one hand‑weeding (HW) at 20 DAS; two HW at 20 & 40 DAS; alachlor 1.5 kg ha-1; alachlor 1.5 kg ha-1 + HW 30 DAS; imazethapyr 0.15 kg ha-1; and imazethapyr 0.15 kg ha-1 + HW 30 DAS, combined with three nitrogen rates (0, 20, 40 kg N ha-1), each treatment replicated thrice. Pre‑emergence imazethapyr 0.15 kg ha-1 + one HW at 30 DAS and two HW at 20 and 40 DAS gave the greatest weed suppression, lowering weed density and dry matter by approximately 82 % at harvest and achieving the highest weed‑control efficiency among all treatments. The imazethapyr + HW package also produced the tallest plant (143.05 cm) and the maximum seed yield (855 kg ha-1), significantly surpassing all other weed‑control options. The integrated weed management practice involving the application of Imazethapyr @ 1.5 kg ha-1 + hand weeding at 30 DAS proved to be the most effective in suppressing weed growth. Nitrogen nutrition further enhanced crop performance: raising the dose to 40 kg N ha-1 delivered the tallest plants both at 50 DAS and harvest and the highest mean seed yield (787 kg ha-1), demonstrating that adequate N amplifies the benefits of effective weed management in sesame.